1995
DOI: 10.1121/1.413096
|View full text |Cite
|
Sign up to set email alerts
|

Interference in detection of interaural delay in a sinusoidally amplitude-modulated tone produced by a second, spectrally remote sinusoidally amplitude-modulated tone

Abstract: Sensitivity to interaural time delays (ITDs) within high-frequency sinusoidally amplitude-modulated (SAM) target tones was measured in the presence of a second, spectrally remote diotic SAM tone (termed an interferer). Targets and interferers were 100% modulated at 250 Hz and each was presented at 77 dB SPL for a duration of 250 ms. The modulations of targets and interferers were either in-phase or out-of-phase. In the first experiment, when the target SAM tone was centered at 4 kHz, interferers were centered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 0 publications
7
35
1
Order By: Relevance
“…At echo delays of 16, 32, and 64 ms, the amount of interference observed for distractors below the frequency of the target in this study were quite similar to those reported by Heller and Trahiotis (1995) for SAM tones at different spectral locations. In both cases, interference effects are somewhere between a factor of 2 to 4, with greater interference found as the distractors were decreased in frequency in spite of the fact that the difference between the target and distractor was increased in magnitude.…”
Section: Low-frequency Dominancesupporting
confidence: 87%
See 3 more Smart Citations
“…At echo delays of 16, 32, and 64 ms, the amount of interference observed for distractors below the frequency of the target in this study were quite similar to those reported by Heller and Trahiotis (1995) for SAM tones at different spectral locations. In both cases, interference effects are somewhere between a factor of 2 to 4, with greater interference found as the distractors were decreased in frequency in spite of the fact that the difference between the target and distractor was increased in magnitude.…”
Section: Low-frequency Dominancesupporting
confidence: 87%
“…When judgments were based on the source, S7 appeared to show considerably less interference when the echo delay was lengthened to 64 ms, while others showed as much or greater than was obtained with an echo delay of 32 ms. Substantial individual differences have been reported in studies of binaural interference, generally on the order of a factor of two (see Heller and Trahiotis, 1995;and Bernstein and Trahiotis, 1995). If one ignores the data obtained with an echo delay of 8 ms in the current study, we find approximately the same amount of interference and the same extent of individual differences.…”
Section: Low-frequency Dominancesupporting
confidence: 69%
See 2 more Smart Citations
“…Qualitatively, the dominance of low-frequency stimuli in the precedence effect is similar to the low-frequency dominance that has been observed in binaural interference (Heller & Trahiotis, 1995;McFadden & Pasanen, 1976;Yang & Grantham, 1997;Zurek, 1985). In each case, spectral dominance may arise from the greater localization strength of lower frequency signals.…”
Section: The Suppression Model Is Inconsistent With Theories Of Relatmentioning
confidence: 52%